PERBEDAAN SKALA NYERI PERSALINAN SEBELUM DAN SESUDAH DIBERIKAN TEKNIK COUNTER PRESSURE MENGGUNAKAN MEDIA BOLA TENIS PADA IBU BERSALIN KALA I DI PUSKESMAS PAMULANG DAN PUSKESMAS BAKTI JAYA TAHUN 2018 - Dian Puspitasari Effendi; Kartika Sari; Boy Subirosa Sabarguna (Jurnal Kesehatan STIKes IMC Bintaro, 2019)
Introduction, pain in the first stage is caused by uterine contractions, cervical opening, vaginal stretch and pelvic floor. One effort to reduce the pain of stage I with nonpharmacology is counter pressure technique using tennis ball media. Methods, using Quasy Experimental Design research with Pre-Experimental Design design with one group pretestposttest design approach. The method used Accidental Sampling, the number of samples in this study as many as 30 respondents. Measurement of pain scale using Numeric Reating Scale (NRS). Data analysis using Marginal Homogeneity Test. Result, before being applied counter pressure technique using tennis ball media got the result of moderate pain as much as 73% and heavy pain as many as 27%, while data after technique of counter pressure using light weight tennis ball become 7% and moderate pain became 93%. Conclusion, the result of research shows that there is influence of counter pressure technique using tennis ball with p value 0,002. Suggestion, perberian counter pressure technique using tennis ball media is very good given to mother of birth in facing labor process especially decrease intensity of pain at first stage of labor.